Application of Impedance Spectroscopy and Surface Analysis to Obtain Oxide Film Thickness. Issue 9 (12th July 2017) - Chen, Yu-Min; Rudawski, Nicholas G.; Lambers, Eric; Orazem, Mark E.
Abstract : The corrosion behavior of ASTM A416 steel in alkaline electrolyte was investigated by electrochemical and surface analysis approaches, including X-ray photoelectron spectroscopy (XPS) and high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). The power-law model was used to extract values for oxide film thickness from constant-phase-element (CPE) parameters obtained as functions of operating conditions. Calibration experiments showed that, despite different silicon content in nominally identical steels, different film thicknesses as observed by HAADF-STEM, and different impedance responses, three samples yielded a common value for ρδ, an important parameter in the power-law model. Application of Monte Carlo simulations showed that values of both ρδ and film thickness δ followed log normal distributions. Application of the power-law model allowed extraction of film thicknesses, yielding 2–6 nm for silicon-rich steel and 1–2 nm for silicon-poor steel.